School nurses' self‐assessed cultural competence when encountering children of foreign origin: A cross‐sectional study. (15th November 2019) - Wahlström, Emmie; Harder, Maria; Granlund, Mats; Holmström, Inger K.; Larm, Peter; Golsäter, Marie
Abstract: The purpose of this study was to investigate associations between school nurses' self‐assessed cultural competence in health visits with children of foreign origin and demographic variables, by using a cross‐sectional design. A Web‐based questionnaire assessing cultural competence and demographic variables was distributed to a nationally representative sample ( n = 816) of school nurses in Sweden. Data were analyzed using regression analysis. School nurses assessed themselves as culturally aware and moderately culturally competent, but not as culturally knowledgeable, culturally skilled, or comfortable in cultural encounters. Cultural competence was related to education in cultural diversity, how often nurses encounter children of foreign origin, and nurses' country of origin. In total, these variables explained 23.6% of the variation in school nurses' cultural competence. Because school nurses regard themselves as moderately culturally competent, a foundation for promoting children's health on equal terms in school health care exists. However, education in cultural diversity combined with other additional strategies is needed to further strengthen school nurses' cultural knowledge, skills, and comfort level in encounters with children of foreign origin.